Rendering unto Caesar : a fascinating story of one man's tenure under nine prime ministers and presidents of Sri Lanka - Weerakoon, Bradman (Colombo : Vijitha Yapa Publications, 2004)
Autobiographical reminiscences of a Sri Lankan civil servant on the head of states he served and the prevailing political conditions.
Keywords: Sri Lanka -- Officials and employees -- Biography; Sri Lanka -- Politics and government